Exploring the Nexus between ESG disclosure and financial risk, exploring how transparent reporting shapes perceptions of risk and influences the decision-making process for investors. - Hareem Atif; Qandeel Alam (Journal of Peace, Development and Communication, 2024)
There is a growing trend in the corporate world to integrate Environmental, Social and Governance (ESG) criteria into the business practices of companies. his shift is driven by a growing awareness of the impacts of business practices on society and the environment, prompting companies to adopt more sustainable approaches. Research has shown that incorporating ESG criteria not only enhances financial performance but also fosters a balanced societal and economic environment (Rajesh & Rajendran, 2020). Still, what exactly is the impact of transparency surrounding ESG issues on financial risk, is still somewhat muddled and calls for more researches on how it changes how people make business decisions and how people invest (Liu, 2022). This literature review is constructed by gathering existing studies and research, then collectively analyzing them with the purpose of defining the factors under which ESG disclosure is likely to influence an organization’s financial risks with a focus on the implications of transparency on investment decisions and corporate planning for sustainable development.